Future time perspective and interpersonal empathy: Implications for preferring autonomy‐ versus dependency‐oriented helping. (21st June 2018) - Chernyak‐Hai, Lily; Halabi, Samer
Abstract : We examined whether potential help givers' future time perspective (FTP) accounts for the decision to give a person in need dependency‐oriented help (i.e., providing the complete solution) or autonomy‐oriented help (i.e., providing the means to solve a problem). In addition, building on past research on the effects of empathy in help giving decisions, the present research explored whether helpers' willingness to offer specific type of help is predicted by the interaction between FTP and interpersonal empathy. We explored FTP as both a personal predisposition (Study 1) and an experimentally induced state of mind (Study 2). The present research provides a novel perspective on theory and research on help giving behaviour, FTP, and empathy, by showing that when interpersonal empathy is high, considerations of the future predict readiness to give help that promotes person's present and future independent coping rather than help that creates and preserves social dependence.